Anticoagulation management post-transjugular intrahepatic portosystemic shunt in portal hypertension associated with myeloproliferative neoplasms. Issue 8 (December 2021) - Abou-Ismail, Mouhamed Yazan; Prchal, Josef T.; Deininger, Michael W.; Parker, Charles J.; Lim, Ming Y.
Abstract : N/A: Portal hypertension (pHTN) complicates myeloproliferative neoplasms (MPNs), and usually occurs due to Budd–Chiari syndrome or splanchnic vein thrombosis. Current management modalities for MPN-associated pHTN include anticoagulation, transjugular intrahepatic portosystemic shunt (TIPS), and orthotopic liver transplant. Data on the thrombotic and bleeding outcomes of this practice is of poor quality, and whether direct oral anticoagulants (DOACs) are effective in this setting is unknown. We describe failure of DOACs to prevent post-TIPS complications in two case reports of patients with MPN-associated pHTN and review the associated literature. We conducted a comprehensive search in Embase (embase.com), Scopus (scopus.org), and PubMed for existing data on MPN-associated pHTN post-TIPS procedure. Four studies ( n  = 251) of patients with pHTN post-TIPS were eligible (MPN, n  = 143). A review of the literature suggests that patients with MPN-associated pHTN may be at higher risk for post-TIPS complications including stent thrombosis and stenosis, compared with other causes of thrombotic pHTN. DOAC use has not been studied in this setting. While further studies to guide optimal management of MPN-associated pHTN post-TIPS are needed, available evidence suggests that life-long anticoagulation is warranted. DOACs should not be considered standard of care because of lack of evidence of efficacy.